2014
DOI: 10.1039/c4ra01850h
|View full text |Cite
|
Sign up to set email alerts
|

Stable anatase TiO2 formed by calcination of rice-like titania nanorod at 800 °C exhibits high photocatalytic activity

Abstract: This paper demonstrates the complete retention (>98%) of anatase TiO2 crystalline phase after high temperature (800 °C) thermal treatment of rice-like TiO2 nanorods (length = 81–134 nm, diameter = 8–13 nm) relative to 100% conversion of the rutile phase after calcination of P25-TiO2 under similar conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The optical properties of the translucent ECrGO/TiO 2 photoelectrodes were analyzed by UV-Vis spectroscopy in transmittance mode ( Figure S4, Supplementary data). A Taucplot representation of the acquired spectra is shown in Figure 2, The TiO 2 electrode reveals an absorption peak at 3.9 eV, and an absorption edge at 3.20 eV, ( Figure 2) in agreement with the literature value for the indirect bandgap of TiO 2 [36]. In ECrGO/TiO 2 electrodes, both the absorption peak and the edge shift to lower energies with respect to the blank TiO 2 electrode.…”
Section: Photoelectrochemical Measurementssupporting
confidence: 86%
“…The optical properties of the translucent ECrGO/TiO 2 photoelectrodes were analyzed by UV-Vis spectroscopy in transmittance mode ( Figure S4, Supplementary data). A Taucplot representation of the acquired spectra is shown in Figure 2, The TiO 2 electrode reveals an absorption peak at 3.9 eV, and an absorption edge at 3.20 eV, ( Figure 2) in agreement with the literature value for the indirect bandgap of TiO 2 [36]. In ECrGO/TiO 2 electrodes, both the absorption peak and the edge shift to lower energies with respect to the blank TiO 2 electrode.…”
Section: Photoelectrochemical Measurementssupporting
confidence: 86%
“…The high level of heat tolerance of the present OAP-containing particles is attributable to the above-mentioned particle morphology exposing ordered facets. It has been reported that rice-like titania nanorods were only stable enough to convert 2% of anatase into rutile at 1173 K [28]. Another possible reason for the heat tolerance is the presence of stabilizers, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…High thermal stability of single crystalline anatase particles has recently been reported for octahedral anatase (OAPs) [48] and nanorice anatase particles [49]. It has been suggested that faceted particles, without crystal-crystal attachment points, leads to the minimization of surface energy and consequently to an increase in the activation energy of anatase to rutile transformation [25].…”
Section: Phase Contentmentioning
confidence: 99%